Apliccation of SIG in the analysis of water quality in the Gualel parish, prior to the mining process, Ecuador - Campos Collaguazo, Edison Fernando; Morocho Andrade, Rodrigo; Veloz Parra, Nancy Paola; Cuadrado Barreto, Geraldo Ariolfo (Tierra Infinita, 2022)
This research was participatory, involving the communities of the parish of Gualel, georeferencing systems were applied to identify the location where sampling will be carried out in order to study the water quality of the micro-watersheds of the river and the calculation of water volume, also proposing conservation alternatives, in order to generate local capacities in the population through the “learn by doing” methodology and that in this way they can continue with the conservation activity in a sustainable manner, complying with established national and international laws and regulations, samples were taken for the development of the research of water in ten places in the sector, where the following results were obtained: the chemical oxygen demand (COD) of all the sectors of the parish is completely high, on average 14.52 mg/l, this is normally caused by the presence of a discharge industrial (pharmaceutical, paper, tannery, oil, food, mining.), Biochemical oxygen demand (BOD5) is completely high value on average of 5.60 mg/l said contamination owes this state to the accumulation of pesticides, dyes, hydrocarbons, phenolic compounds. The water flow of the sectors is an average of 0.412444 m3/s, which gives us an annual volume of water of 13,006,833.98 m3/year. It is recommended to implement a treatment plant and a training process for the management of chemical inputs.
Keywords: water quality; river micro-basin; conservation